Board Gender Diversity and Financial Reporting Quality in Nigeria: Moderating Role of Auditor Quality - Soyemi, Kenny Adedapo; Adebayo, Sunday Aderogba; Fatai, Ganiu Abiodun (The Journal of Accounting and Management, 2024)
Arising from renewed interest on studies on gender exemplification on board, coupled with mixed findings noticeable therein, this study contributes to literatures, especially in emerging economies, on relationship between women representation on board and financial reporting quality (proxied with accrual and real earnings management) in Nigeria. Besides, the role of audit quality in moderating the aforementioned connection is also examined. Data were collected from annual reports and audited accounts of 50 quoted nonfinancial firms that were purposively selected for 7 years (2014-2020). While random effect OLS regression result provides no evidence of nexus between female directors and accruals earnings management, fixed effects OLS regression supports female representation on board, in order to hinder incidence of real earnings manipulation by management. However, this paper could not provide empirical evidence on the moderating role of audit quality, in both cases. Therefore, more women representation on board should be sustained, and improved upon, perhaps, through legislation on quota, to curb managers’ opportunistic behavior in undertaking real manipulating of earnings, thereby enhancing quality of financial reporting. Besides, this is another sure way to building women entrepreneurs and innovators.